Critical Literacy and Pedagogical Transformation among Prospective Indonesian Language Teachers - Susetya, Hemas Haryas Harja; Sukardi, Mochamad Ighfir (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The critical reading ability of prospective teacher students remains a serious issue in higher education, particularly in regions with low literacy levels such as Probolinggo Regency, which has the lowest Community Literacy Development Index (IPLM) in East Java, thus demanding transformative pedagogical strategies to foster students' reflective reasoning and discourse awareness. This study aims to examine the effectiveness of a critical literacy approach in improving the critical reading ability of students in the Indonesian Language Education Study Program at Zainul Hasan Genggong University (UNZAH) through strengthening six dimensions of critical thinking according to Facione's model, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. This study employs a quasi-experimental design with a non-equivalent control group, involving 50 students divided into experimental and control classes, and analyzes data through ANCOVA testing to determine the effect of treatment after controlling for initial scores (pretest). The results show a significant improvement in the experimental group (p < 0.001), particularly in the interpretation and inference dimensions, and confirm that the critical literacy approach is the main factor in improving students' posttest scores. Thus, the critical literacy approach proves effective as a pedagogical strategy in Islamic higher education to develop teachers who are not only capable of reading texts but also of reading the world critically, reflectively, and with intellectual responsibility.